(untitled) (Research, Society and Development, 2022)
The objective was to study the productivity and quality of the hybrid zucchini of brand Seminis® in different cultivation environments with different doses of coffee straw in coverage. The experiment was conducted at the Regional Unit for Research and Development of Adamantina/SP, of APTA Regional. The experimental design was randomized blocks in a 2x5 factorial scheme. The treatments were divided into field and protected environments and five doses of coffee straw (0; 2.5; 5; 10 and 20 t ha-1). Five replicates per treatment were evaluated, with four plants per plot. Length, diameter, fresh mass and soluble solids of the fruits were analyzed. The data were submitted to analysis of variance by the F Test and the means were compared by the Tukey Test at a 5% significance level. The SISVAR program was used for statistical analysis. It was identified that the length of the zucchini was superior in the field cultivation. In relation to the diameter of the fruit, parity was observed between the results. The soluble solids values ​​indicated significantly different results between the cultivation environments. It was observed that in field cultivation the number of fruits per plant was significantly higher compared to protected cultivation. The average fresh mass per fruit was higher in field cultivation. It was concluded that field cultivation is the most economically viable system for the production of Italian zucchini in the region under study. The protected environment restricted the access of pollinating insects resulting in a lower number of fruits per plant. The use of coffee straw as a cover did not interfere with the development and productivity of the hybrid Italian zucchini PX7051.